1994
DOI: 10.1523/jneurosci.14-08-04740.1994
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioids inhibit induction of long-term potentiation in the dentate gyrus of the guinea pig hippocampus

Abstract: NMDA receptor-mediated long-term potentiation (LTP) of dentate granule cell responses to perforant path stimulation was inhibited by the kappa 1 opioid receptor agonist U69,593. This inhibition was reversed stereospecifically by naloxone and blocked by the selective kappa 1 antagonist norbinaltorphimine (NBNI). NBNI, by itself, had no effect on LTP induced by threshold stimulation but significantly enhanced LTP from more prolonged stimulation. This effect of NBNI suggests that endogenous opioids can regulate L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 41 publications
4
39
1
2
Order By: Relevance
“…It is conceivable that released enkephalins may act at 6 receptors on interneurons to hyperpolarize their dendrites, which reduces calcium influx through NMDA channels and hence inhibits induction of LTI? Different opioid receptor subtypes are known to play distinct roles in modulating LTP of excitatory synaptic signals in the hippocampus (Bramham et al, 199la;Xie and Lewis, 1991;Wagner et al, 1993;Weisskopf et al, 1993;Terman et al, 1994). Our data suggest that this is also the case for opioid regulation of LTP in inhibitory circuits.…”
Section: Discussionsupporting
confidence: 59%
“…It is conceivable that released enkephalins may act at 6 receptors on interneurons to hyperpolarize their dendrites, which reduces calcium influx through NMDA channels and hence inhibits induction of LTI? Different opioid receptor subtypes are known to play distinct roles in modulating LTP of excitatory synaptic signals in the hippocampus (Bramham et al, 199la;Xie and Lewis, 1991;Wagner et al, 1993;Weisskopf et al, 1993;Terman et al, 1994). Our data suggest that this is also the case for opioid regulation of LTP in inhibitory circuits.…”
Section: Discussionsupporting
confidence: 59%
“…The hippocampus is enriched with glucocorticoid receptors and is crucially involved in regulating stress effects on synaptic plasticity and learning and memory (Shors et al, 1989;Oitzl and de Kloet, 1992;Pavlides et al, 1996;Xu et al, 1997;de Quervain et al, 1998;McEwen, 1999;Kim and Diamond, 2002). On the other hand, both synaptic plasticity (Terman et al, 1994;Little and Teyler, 1996;Mansouri et al, 1999;Pu et al, 2002) and behavioral studies (Fan et al, 1999;Lu et al, 2000;Mitchell et al, 2000) support the view that the hippocampus is involved in opiate addiction, and in other drugs addiction as suggested recently (White, 1996;Berke and Hyman, 2000;Hyman and Malenka, 2001;Nestler, 2001a;Vorel et al, 2001). …”
Section: Reinforcing Effect and Associative Learningmentioning
confidence: 77%
“…Previous studies have shown that stress or glucocorticoids block or facilitate memory and affect LTP and long-term depression (LTD) in the hippocampus (Shors et al, 1989;McEwen, 1994;Diamond et al, 1996;Kim et al, 1996;Xu et al, 1997Xu et al, , 1998ade Quervain et al, 1998;Conrad et al, 1999;Mizoguchi et al, 2000). Similarly, opiates affect cognitive function (Beatty, 1983;Classen and Mondadori, 1984;Guerra et al, 1987;Li et al, 2001) facilitate (Mansouri et al, 1999) or inhibit (Terman et al, 1994;Pu et al, 2002) LTP, and facilitate LTD (Wagner et al, 2001) in the hippocampus. Furthermore, stress modifies morphine responses in behavior (Olley et al, 1990;Deroche et al, 1992), and morphine influences the effect of stress on synaptic plasticity and behavior (Fratta et al, 1977;Shors et al, 1990;Scheggi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These released dynorphins were found to selectively bind to kappa opioid receptors after release (Wagner et al, 1991). Focal stimulation of dynorphin-containing pathways caused presynaptic inhibition of excitatory synaptic transmission in hippocampus that could be selectively blocked by kappa receptor antagonism (Wagner et al, 1993;Weisskopf et al, 1993;Drake et al, 1994;Terman et al, 1994). These studies are summarized in more complete reviews (Castillo et al, 1996;Simmons and Chavkin, 1996) and diagrammed in Fig.…”
Section: Neurotransmitter Properties Of Dynorphinmentioning
confidence: 99%